(untitled) (Research, Society and Development, 2020)
This paper sought to investigate the factors that influence student inattention, and also to verify the possibility of reducing it with the use of Augmented Reality (AR). This research was attended by 54 students in the 2nd grade of High School/Technical. Initially, a survey was conducted using a questionnaire to identify the reasons that cause learning damage. This first step revealed that excessive use of smartphones and parallel conversations represent ≅83% of the elements that hinder the teaching-learning process. In a second moment, an experiment was performed with the use of an AR application in the station rotation methodology. Results show evidence of the student’s broadening and understanding of the subject, support for clarifying content and guiding the reasoning.